(3JMdjd GdEbJUGO GdOhdjs - (3ghTjGQ(B, (3eYQhas ((3YeGf(B:s (3OGQ LQjQ(B,s, 2006)
(3CSGSjGJ GdEbJUGO GdOhdj(B-(3JMdjd GdJWhQ GdJGQjNj ddEbJUGO GdOhdj(B-(3JMdjd hbGFY MOjKI aj GdEbJUGO GdOhdj(B-(3GdEJaGbjGJ GdYGeI ddJYQjaGJ hGdJLGQI hefXeI GdJLGQI GdYGdejI(B-(3ejRGf GdeOahYGJ GdOhdjI(B-(3CShGb GdUQa GdCLfHj(B-(3ejRGf GdeOahYGJ GdOhdjI hCShGb GdUQa GdCLfHj(B-(3GdSjGSGJ GdEbJUGOjI GdOhdjIs
Keywords: (3CShGb GdUQas; (3GdEbJUGO GdOhdjs; (3GdJLGQI GdYGdejIs; (3GdeOahYGJ GdOhdjIs